Cover Image. Issue 6 (26th November 2018) - Farooq, Umer; Ahmed, Zaheer; Naeem, Khalid; Bertram, Miranda; Brito, Barbara; Stenfeldt, Carolina; Pauszek, Steven J.; LaRocco, Michael; Rodriguez, Luis; Arzt, Jonathan
Abstract : The cover image, by Umer Farooq et al., is based on the Original Article Characterization of naturally occurring, new and persistent subclinical foot‐and‐mouth disease virus infection in vaccinated Asian buff alo in Islamabad Capital Territory, Pakistan, DOI:10.1111/tbed.12963 .